Noir : a novel - Moore, Christopher, 1957- (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"From repeat New York Times bestselling author Christopher Moore comes a brand new standalone novel set on the mean streets of San Francisco in the aftermath of World War II. Absurdly outrageous, sarcastically satiric, always entertaining--Christopher Moore is back!"--